2022
DOI: 10.2298/vsp210521092d
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptomatology among children and adolescents exposed to the COVID-19 pandemic: A systematic review

Abstract: Background/Aim: Children and adolescents are the sensitive groups for the development of mental disorders during the crisis. The aim of this systematic review is to assess the impact of the COVID-19 pandemic regarding anxiety and depressive symptomatology in this population. Method: Investigation is based on a Systematic Review followed by PRISMA protocol including Ovid MEDLINE, Embase, Global Health and APA Psyc Info data bases to identify relevant studies reporting anxiety and depressive sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Children and adolescents are vulnerable groups for developing mental disorders in times of crisis. Age ( children , adolescents ), gender ( especially boys ), depression, and stress were the potential key factors for Internet addiction [5,12 ▪▪ ,61]. In Indonesia, increased hours of Internet use, internalization, externalization, low prosocial behaviour, and sleep disturbances were risk factors for Internet addiction among 2932 adolescents (mean age = 17.38 ± 2.24 years; women, 78.7%).…”
Section: Vulnerable Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children and adolescents are vulnerable groups for developing mental disorders in times of crisis. Age ( children , adolescents ), gender ( especially boys ), depression, and stress were the potential key factors for Internet addiction [5,12 ▪▪ ,61]. In Indonesia, increased hours of Internet use, internalization, externalization, low prosocial behaviour, and sleep disturbances were risk factors for Internet addiction among 2932 adolescents (mean age = 17.38 ± 2.24 years; women, 78.7%).…”
Section: Vulnerable Groupsmentioning
confidence: 99%
“…As children, adolescents, and young adults (university students) are vulnerable groups, prevention programs focused on coping strategies should be implemented in elementary, middle, and high schools, and universities. Also, as mental health should become a priority for governments, the current pandemic could be an opportunity to highlight the importance of mental wellbeing and to invest in clinical training, treatments, and mental health research [12 ▪▪ ,26]. During these unprecedented times, the role of extended family and professional support for vulnerable individuals should be underscored [61].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, threat perceptions and economic dependencies differ among EU member states (Von der Burchard and Rinaldi, 2023), as they do between the USA and Europe. Beijing has succeeded in retaining pockets of influence in Europe, namely, in the Western Balkans (Stanicek and with Tarpova, 2022; Djurdjevic, 2022). Except for Hungary, Central and Eastern European countries tend to be more hawkish toward China than their Western and Southern European counterparts.…”
Section: The Limits Of Transatlantic Convergencementioning
confidence: 99%
“…Children and adolescents are one of the most vulnerable groups in this pandemic in terms of the development of psychological abnormalities (39,40). It was found that their stress during this epidemic mainly stemmed from the inability to participate in social activities/normal daily activities and important plans/events being canceled or postponed (41).…”
Section: Effect Mechanism In Cluster 2: Changes In Stress and Emotionsmentioning
confidence: 99%